Future of Nuclear Medicine – Impact of New Radiopharmaceuticals and of Alternative Methods such as Nuclear Magnetic Resonance - Pfannenstiel, P.; Rinck, P. A. (Nuklearmedizin - NuclearMedicine, 1984)
Nuclear medicine (NM) is returning to its origin by studying more and more metabolic signals using new positron or single photon emitting radiopharmaceuticals. Much of the success that has been achieved by PET is now being transferred to SPECTtechniques. In contrast to static planar scans the changing tissue concentration of radiotracers can now be quantified. In this respect radioimmunodetection using monoclonal antibodies has a tremendous future. It is quite probable that 99mTc will continue to be the principle radionuclide. Especially radiopharmaceuticals for “hot spot”-imaging will be important in the near future, for example radioactively labelled blood cells. NM has a unique contribution to offer to nuclear magnetic resonance (NMR) because of its emphasis on physiologic as well as anatomic imaging parameters. NM can interact with the new revolutionizing technology of NMR in two ways: NM can help to understand NMR and NMR can help to identify regions of interest to be studied by NM. For example, we cannot see metabolic processes of the brain in NMR which are seen by biological radiotracers such as dopamin receptors in NM. However, there is no doubt, that NMR will also have a negative impact on NM. The potential value of NMR for in vivo biochemical analysis seems to be tremendous. The additional information gained by NMR about metabolic processes may well change our entire understanding of health and disease. The advantage that NM procedures can be performed on an outpatient basis will apply to NMR as well. NM and NMR will be complementary modalities in the future.